Violence and the word - Cover, Robert; Pedroso Flores, Maurício (Revista da Faculdade de Direito do Sul de Minas, 2019)
: Legal interpretation’ takes place in a field of pain and death. This is true in several senses. Legal interpretive acts signal and occasion the imposition of violence upon others: A judge articulates her understanding of a text, and as a result, somebody loses his freedom, his property, his children, even his life. Interpretations in law also constitute justifications for violence which has already occurred, or which is about to occur. When interpreters have finished their work, they frequently leave behind victims whose lives have been torn apart by these organized, social practices of violence. Neither legal interpretation nor the violence it occasions may be properly understood apart from one another. This much is obvious, though the growing literature that argues for the centrality of interpretive practices in law blithely ignores it.